Binômio mãe-filho: estudo epidemiológico e de base populacional desenvolvido em maternidades de baixo e alto risco - Carvalheira, Ana Paula Pinho [UNESP] (2016)
Objectives: a) Describe the adequacy of prenatal care site, according to gestational risk factors. b) Identify factors associated with maternal and perinatal outcome in pregnant women with hypertension; c) Compare the sociodemographic characteristics of the pregnant women, the care given to the mother-child binomial at delivery and conditions of newborns at birth in public and private hospitals. Method: This is an epidemiological, observational study conducted with a total of 1343 pregnant women in a medium sized city in the state of São Paulo - Brazil, whose deliveries occurred from January to June 2012. Using instruments built specifically for this study, containing the variables of interest. Results: Of the 291 pregnant women/mothers who were attended at high risk prenatal, 131 (45.0 %) had no indication for such and should be being followed in primary care or private services. Women who had previous medical conditions that indicated specialized follow-up, totaled 39 cases and 19 (48.7 %) received this type of care. Among the risk factors of current pregnancy that require referral to high risk, were 198 cases, of which 90 (45.5%) were followed in this level of complexity. There were 31 at high risk (39.2%) of the 79 cases classified as requiring referral to urgent/emergency obstetric care. The group of hypertensive disorders was the group most frequently kept in primary care, despite having an indication of high risk prenatal for disease prior to pregnancy, illness during the pregnancy or urgent/emergency condition. As for maternal factors associated with hypertension, the only socio-demographic variable with the association was the age older than 35 years (OR = 1.64, 95% CI 1.02 to 2.64, p = 0.043); independently, it was observed among women who had hypertension during pregnancy, a higher rate of neonatal resuscitation (OR = 2.24, 95% CI 1.31 to 3.83, p = 0.003), preterm birth (OR = 3.47, 95% CI 2.09 to 5.77 and p <0.001) and low birth weight (OR = 2.33, 95% CI 1.33 to 4.09, p = 0.003). There was a positive association between giving birth in a public hospital and being a teenager (OR = 4.21, CI = 2.64 to 6.73), having elementary education (OR = 10.9, CI = 6.94 to 17.39), being primiparous (OR = 1.54, CI = 1.21 to 1.96), not having a partner (OR = 2.65, CI = 1.74 to 4.04), having unplanned pregnancy (OR = 3.23, CI = 2.51 to 4.15), having held up to six prenatal consultations (OR = 3.10, CI = 2.04 to 3.23) and having prenatal care in public service (OR = 49.75, CI 32.80 to 75.47). As for care during labor, birth in a public hospital was protected from performing cesarean delivery and elective caesarean section (OR = 0.001, CI = 0.0004 to 0.006) and other routine procedures, whose evidence points losses. Showed a significant association between birth in the public hospital and adverse neonatal outcomes, including prematurity (OR = 1.63, CI = 1.12 to 2.36), low birth weight (OR = 2.26, CI = 1.46-3, 51) and need for resuscitation (OR = 3.32, CI = 1.97 to 5.59). Even with these negative conditions, born in the public hospital favored the exclusive breastfeeding at discharge. Conclusion: It is important to identify the gestational risk factors as early as possible, promoting agility in service, defining the need for care and technological density that should be offered to users at all times. Women over 35 require even more care during the prenatal follow-up for early detection of pressure changes. Controlling the hypertensive disorders in pregnancy and intervening in a timely manner may result in no maternal complications and health problems in the fetus. Both the public and the private hospitals, there have been aspects that deserve and effective measures and actions by health professionals, as well as managers, envisisioning the success of maternal and child care, especially with regard to better neonatal outcomes.